Hungarian Monitoring, 2 August 1989 . [Magyar rádiófigyelő], 1989. augusztus 2 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - New Polish premier's program - V. Havel taken into custody in Prague Domestic Affairs: - Three-sided political talks now conducted in private; trench warfare - Hungary also mentioned at CPSU Politburo session - Krishna followers' conference Economy: - Zsigmond Járai thinks lack of political, economic and convertible forint is keeping Western financiers from investing in Hungary - Hungarian government does not want debt relief from the West but would like to receive credit more easily Külpolitika: - Az új lengyel miniszterelnök programja - Prágában ismét őrizetbe vették V. Havelt Belpolitika: - A háromoldalú politikai tárgyalások zártkörűvé váltak; állóháború - Magyarországról is szó volt az SZKP PB-nak ülésén - Krisna Életűek sajtókonferenciája Gazdaság: - Járai Zsigmond szerint a politikai, gazdasági, és a konvertibilis forint hiánya távol tartja a nyugati tőkét a magyarországi befektetéstől - A magyar kormány nem kér adósságkönnyítést a Nyugattól, csak azt szeretné, ha könnyebben juthatna hitelhez